Neurofibromatosis Type 1: Modeling CNS Dysfunction - Gutmann, David H. (Society for Neuroscience, 2012)
Neurofibromatosis type 1 (NF1) is the most common monogenic disorder in which individuals manifest CNS abnormalities. Affected individuals develop glial neoplasms (optic gliomas, malignant astrocytomas) and neuronal dysfunction (learning disabilities, attention deficits). Nf1 genetically engineered mouse models have revealed the molecular and cellular underpinnings of gliomagenesis, attention deficit, and learning problems with relevance to basic neurobiology. Using NF1 as a model system, these studies have revealed critical roles for the NF1 gene in non-neoplastic cells in the tumor microenvironment, the importance of brain region heterogeneity, novel mechanisms of glial growth regulation, the neurochemical bases for attention deficit and learning abnormalities, and new insights into neural stem cell function. Here we review recent studies, presented at a symposium at the 2012 Society for Neuroscience annual meeting, that highlight unexpected cell biology insights into RAS and cAMP pathway effects on neural progenitor signaling, neuronal function, and oligodendrocyte lineage differentiation.